Socio Scientific Issue Based Interactive Learning Module in Islamic Religious Learning and Ethics at the Basic Level - Sholahuddin, Agus Moh; Suttrisno, Suttrisno; Yulia, Nurul Mahruzah; Roin, Usman (LP. Ma'arif Janggan Magetan, 2026)
This study aims to develop a Socio Scientific Issue (SSI) Based Interactive Learning Module in the subject of Islamic Religious Education and Ethics at the basic level by using the ADDIE development model which involves the stages of needs analysis, design, development, limited trials, implementation, and evaluation. The research subjects involved 120 elementary school students in Bojonegoro. Data collection instruments include expert validation sheets, student response questionnaires, and observation of student involvement and communication in learning. This module is designed to integrate socio-scientific issues into learning so that it is able to foster an understanding of Islamic values as well as 21st century skills, especially students' active participation and communication skills. The validation of the feasibility of the module was carried out by three experts with very decent results, namely 98% media experts, 97% linguists, and 95% learning experts. Implementation trials showed a significant increase in student engagement, with participation increasing by up to 85% compared to conventional learning, and communication skills increasing by 92%. The implications of this research emphasize the effectiveness of SSI-based modules in enhancing learning quality, strengthening student engagement, and integrating Islamic values with critical thinking and communication skills. This model can support innovative and character-based learning in primary education. Future research may expand implementation to different contexts, introduce more complex SSI themes, and evaluate long-term impacts on students’ moral and critical reasoning development.